PENGALAMAN PERAWAT MENGATASI DAMPAK HOSPITALISASI PADA ANAK - Remilda Armika Vianti (LPPM Universitas Pekalongan, 2020)
Hospitalization is a process for a reason or an emergency. This process requires the child to stay in the hospital. Hospitalization can cause anxiety and fear to all levels of age of children and parents. Fear and anxiety because of injury to the body, new environment and separation. This condition will affect children development. Nurse's role in minimizing the stress on the children as a result of hospitalization is very important, so that nurses need to understand the concept of the stress of hospitalization and nursing care principles through approach to meet development of positive effects and to minimize the negative effects of hospitalization. The aim of the study is to discover experience of nurses in overcoming the impact of hospitalization on children in Dr. M.Ashari PemalangGeneral Hospital, by taking sample of 6 participants. This study uses qualitative research with a phenomenological approach, the data obtained with in-depth interview and recorded using ic recorder with the consent of the respondent. The data obtained and then is classified by thema This study showed that 1) nurse understand the fear and anxiety, 2) the reaction of children to hospitalization, 3) nurse’s response to children with hospitalization, 4) barriers to cope with the child’s hospitalization, 5) difficulty facility, 6) efforts to nurse the children cope with hospitalization, 7) nurse child support adaptation. Advice nurse increased efforts implementing adaptation model of nursing care S.C.Roy and caring K.M. Swanson.